Er:YAG laser treatment of urinary incontinence after failed TOT/TVT procedures. (September 2020) - Erel, C. Tamer; Fernandez, Luis Diego Carazo; Inan, Deniz; Makul, Melike
Highlights: Non-ablative Er:YAG smooth mode laser may be an alternative choice of treatment for the SUI symptoms in patients who previously had failed TOT/TVT procedures. Abstract: Objective: To determine if the Er:YAG laser can improve the symptoms of SUI patients after previously failed TOT/TVT procedures. Study Design: This retrospective study includes the data of patients who were recruited from two different out-patient clinics of Obstetrics and Gynecology Department. 25 women with persistent SUI after failed TOT/TVT operations and 25 women who previously did not receive either any type of surgical treatment procedure or non-invasive treatment modalities for SUI. Er:YAG laser with 2940 nm was used in the treatment procedure for SUI setting. The patients were evaluated on the basis of ICIQ-SF before and after the procedure. The severity of SUI symptoms was graded. According to the differences in the ICIQ-SF between before and after the procedure, the percentage of improvement was graded as good responders (≥50 %) or poor responders (<50 %).The duration of the treatment effect was evaluated in follow-ups with relation to maximum improvement time (MIT) and total improvement time (TIT). Results: The SUI patients who previously had failed TOT/TVT operations, had significantly higher initial ICIQ-SF score (p = 0.013). Non-ablative Er:YAG laser treatment significantly and similarly improved the severity of SUI symptoms in both groups (p = 0.000 for failed TOT/TVT group and p = 0.001 for non-TOT/TVT group, respectively). The women who were good responders, were younger (p = 0.012) and had less number of years in menopause (p = 0.011). The effect of Er:YAG laser treatment lasted longer among the SUI women in the good responders group (p = 0.000 for MIT and p = 0.000 for TIT, respectively). Conclusions: Non-ablative Er:YAG smooth mode laser is an alternative choice of treatment for the SUI patients who previously had failed TOT/TVT procedures. Its effect lasts longer especially in younger and early postmenopausal women.